2020
DOI: 10.1177/2158244020920608
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Public Open Space per Inhabitant in the Kingdom of Saudi Arabia: A Case Study of the City of Jeddah

Abstract: Public open spaces are essential for residents’ social interactions and recreational activities, improving well-being as well as offering economic and environmental benefits. Saudi Arabia is aiming to enhance the quality of life in all its cities through different national programs and projects. One of the key performance indicators is increasing public open space per capita from 3.47 to 3.9 m2 by 2020. This study measured the current public open space per inhabitant in Jeddah using a geographic information sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 42 publications
0
24
0
1
Order By: Relevance
“…Thus, GSs have an immense impact on the overall sustainability of the urban environment. However, up to now, very limited focuses have been given to the quantitative assessment of GSs across the cities of Saudi Arabia [32]. Thus, from a review of the previous literature, some notable gaps were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, GSs have an immense impact on the overall sustainability of the urban environment. However, up to now, very limited focuses have been given to the quantitative assessment of GSs across the cities of Saudi Arabia [32]. Thus, from a review of the previous literature, some notable gaps were identified.…”
Section: Introductionmentioning
confidence: 99%
“…As per these guidelines, the integration of green spaces has been significantly prioritized in the decision-making framework. Apart from this, special focus has been given on the availability as well as the accessibility of POS in Saudi cities by the National Transformation Programme (NTP) in Vision 2030 [29,30]. The Saudi government is concerned with the provision of POS to make cities more livable and has invested huge sums to enhance the accessibility of POS [29,30,63].…”
Section: Shanghai (China) Fan Et Al 2016mentioning
confidence: 99%
“…Apart from this, special focus has been given on the availability as well as the accessibility of POS in Saudi cities by the National Transformation Programme (NTP) in Vision 2030 [29,30]. The Saudi government is concerned with the provision of POS to make cities more livable and has invested huge sums to enhance the accessibility of POS [29,30,63]. At a local scale, municipalities must focus on the restoration and management of POS for urban environmental sustainability and improve the quality of life of city dwellers.…”
Section: Shanghai (China) Fan Et Al 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…POS were neglected in the past and given low priority until the announcement of Saudi Arabia's Vision 2030. In its key performance indicators, the Vision 2030 National Transformation Program (NTP) highlighted the importance of enhancing the urban landscape in Saudi cities by increasing residents' access to POS and improving POS availability per inhabitant [71,80]. In addition, the NTP established several programs to support Vision 2030, including the Quality of Life Program, which aims to make Saudi cities more livable [70].…”
Section: Public Open Space Provision In Saudi Arabiamentioning
confidence: 99%